2012
DOI: 10.5005/jp-journals-10015-1180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acidic Environment on the Push-out Bond Strength of Biodentine™

Abstract: Introduction: An apical sealing material may be exposed to an inflamed environment with low pH levels. The change in physical and chemical properties of mineral trioxide aggregate has been well-documented in the presence of low pH. However, on literature search there is no documentation of the effect of low pH on Biodentine TM .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…These results may be explained by on the basis of calcium chloride present in the liquid of BD provided by the manufacturer. Although both materials produce the same chemical compounds, it may be speculated that this reaction is more efficient in BD, which has a shorter setting time (32) . Moreover, BD permits a higher release of bioactive ions (calcium and hydroxyl ions) than MTA during the initial setting, reducing ion release over time and consequently producing more favorable conditions for pulp repair (33) .…”
Section: Discussionmentioning
confidence: 99%
“…These results may be explained by on the basis of calcium chloride present in the liquid of BD provided by the manufacturer. Although both materials produce the same chemical compounds, it may be speculated that this reaction is more efficient in BD, which has a shorter setting time (32) . Moreover, BD permits a higher release of bioactive ions (calcium and hydroxyl ions) than MTA during the initial setting, reducing ion release over time and consequently producing more favorable conditions for pulp repair (33) .…”
Section: Discussionmentioning
confidence: 99%
“…Guneser et al showed that irrespective of the irrigation solution, the force needed for displacement of Biodentine from root dentine is significantly higher than the force required for MTA. 53…”
Section: Push Out Bond Strengthmentioning
confidence: 99%